Contextual Meaning in the novel Kau, Aku dan Sepucuk Angpau Merah by Tere Liye - Fajriyatil Masruroh; Sitti Juniarsih (Penerbit Hellow Pustaka, 2024)
This study aims to examine the contextual meaning contained in the novel Kau, Aku, and Sepucuk Angpau Merah by Tere Liye. The method used in this study is a qualitative descriptive method. The data source in this study is the novel Kau, Aku, and Sepucuk Angpau Merah by Tere Liye. The data collection technique is through an in-depth reading technique of the novel. This reading is done by observing every aspect of the text. Contextual meaning is greatly influenced by the social situation, time, place, and the relationship between the speaker and the listener. The results of this study in the form of a discussion of quotations in the novel, it was found that many words or expressions have different meanings from their literal meanings. For example, expressions such as